Influence measures based on confidence ellipsoids in general linear regression model with correlated regressors. Issue 15 (17th November 2016) - Açar, T. Söküt; Özkale, M.R.
ABSTRACT: In this paper, we investigated the Andrews–Pregibon (AP), COVRATIO and Cook–Weisberg (CW) statistics to determine the influential observations on the confidence ellipsoids in linear regression model with correlated errors and correlated regressors. A real example and a Monte Carlo simulation study are given to detect the effects of autocorrelation coefficient and ridge parameter on the AP, COVRATIO and CW statistics.